Enhancement on Mechanical and Thermal Properties of PLA Biocomposites Due to the Addition of Hybrid Sisal Fibers - Zhihua Zhu; Hongwu Wu; Chaolin Ye; Wuchang Fu (Journal of Natural Fibers, 2017)
Hybrid sisal fibers (HSFs) were made by mixing untreated sisal fibers (USFs) with alkali treated sisal fibers (ASFs), and blended with PLA matrix to make PLA/HSFs composite. It was found that the reinforced effect of HSFs was better than that of ASFs. Impact strength and crystallinity of PLA/HSFs had obvious improvements. β crystal of PLA was found from the XRD graph of PLA/HSFs, which may lead to an enhance in the impact strength and thermal stability.